Naṅ paʼi sde pa gsum gyi chos ʼkhor gyi mdo ; daṅ, ʼPhags pa gnas brtan sde paʼi mdo gsum: Bāuddhoṃ ke tīna nikāyaoṃ ke dharmacakrapravartasūtra evaṃ sthaviravāda ke tīna sutta = Dharmacakrapravartanasutra of three Buddhist schools and three Suttas of Theravada tradition = Bauddhoṃ ke tīna nikāyoṃ ke Dharmacakrapravartanasūtra evaṃ sthaviravāda ke tīna sutta - Dorjee, Lobsang (Bibliotheca Indo-Tibetica series, 2010)
Criticaly edited, annotated and translated into Tibetan and English, the two root texts on Turning the wheel of Dharma (Dharmacakrapravartanasutra) of three Buddhist schools and three suttas of Theravada.tradition